Dipole-induced processes in HeH+ produced by an excited Li(2p) neighbor: from charge transfer to virtual photon dissociation, and formation of LiH and LiHe - Cabrera-Trujillo, Remigio; Vendrell, Oriol; Cederbaum, Lorenz S. (Physical review, 2022)
Dipole interaction between neighbor systems is of importance in the behavior of atoms and molecules as it produces distortion in the electronic structure of the system. In this work, we study the dipole processes in a HeH+ molecule induced by an initially excited lithium atom placed at an R0 distance from the center of mass of the molecule. The electronic and nuclear degrees of freedom are treated by the electron-nuclear dynamics approach as it allows a time-dependent description of the electronic and nuclear dynamics. The energy transferred from the neighbor excited lithium atom to the HeH+ molecule is distributed into several channels depending on the initial vibrational state of the HeH+ and initial R0 separation. We find that several processes are induced by the dipole interaction. Among these, we find that the charge-transfer channel from the Li onto the ionic molecule HeH+ is the dominant outcome. Also, we find that a virtual photon dissociation process takes place via a dipole interaction that induces nuclear motion of the molecule through an electronic relaxation of the initial lithium 2p electron to the 2s state or to the 1s state of the He or H atom of the neighbor system, as well as vibrational intermolecular energy transfer. We report dissociation of the HeH+ molecule followed by chemical rearrangement leading to the formation of LiH and LiHe molecules and their respective charged ions. We find that deexcitation occurs on femtosecond while the molecular dissociation on picosecond time scales. Consequently, the dipole interaction between neighbors induces a richer dynamics.
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 30.06.2022